Evaluation of Lipid Profile and Cytogenetic Disturbance in Hypertensive Patients - Tayseer Shamran Al-Deresawi (Journal of Global Pharma Technology, 2018)
In the purpose of studying the differences between normal and hypertensive people, this study was focused on estimating these differences using lipid profile and cytogenetic effects. To initiate this process, sampling of blood from 33 patients and 25 healthy individuals of 3 different age categories was performed in Al-Zahra Teaching Hospital and Al-Karama Hospital in Wasit province, Iraq. These blood samples were subjected to measuring cholesterol, triglycerides (TG), HDL, and LDL. Moreover, blood lymphocytes were employed to visualizing certain cytogenetic disturbance indicators such as mitotic index (MI), nuclear division index (NDI), and Micronucleus (MN). When looked at patient group, the results identified significant (p˂0.05) differences between groups revealing increases in all the tested lipids except decreases in HDL. In case of cytogenetic effects, significant increases (p˂0.05) were seen in the MI, NDI, and MN in all patients at all ages. Here, the results indicate important role of blood hypertension in having specific lipid profile and most importantly the changes in the activity of the cells to increase unwanted proliferation.Keywords: Blood Hypertension, Lipid Profile, Cytogenetic.